Ocean hypoxia: The science of climate change in the sea - Francis Chan; Inna Sokolova; Kay Vopel (Scientific Reports)
Abstract The oxygen inventory of the global ocean is declining. This phenomenon, known as ocean deoxygenation, has emerged as a fundamental pathway for climate change to alter marine ecosystems. An important concern is how this global oxygen decline will manifest in coastal and oceanic systems that are already subject to low oxygen, or hypoxic conditions. There is also a clear need to understand how the intensification and/or expansion of hypoxia will affect ocean food webs and biogeochemical cycles. Building a predictive understanding of ocean hypoxia is a multi-scaled and multi-disciplinary research endeavor. Recent advances in ocean observation, experimental biology, and ecosystem modeling are being applied to ocean hypoxia research to reshape our understanding of the future ocean.